Health Service Reform in Bekasi City - Wedi, Agus; Suryani, Yuli; Br Sembiring, Emi; Prihantini, Shelfie (Borong Newinera Publisher, 2025)
This paper examines the changes in health service reform in Bekasi City. Health services are an important part, especially with regard to optimizing health implementation at the most basic level. This study is important because it describes the potential and challenges faced by the Bekasi City government in seeking changes for better health services. This study belongs to the category of descriptive qualitative research, using two sources, namely primary sources as the main source including information and data on health service reports in various hospitals in Bekasi City and secondary sources as a source of reinforcement including various scientific studies related to health service reform. The data analysis techniques used are data condensation, data display, and conclusion drawing/verification. This paper has two conclusions, namely first, the Population Identification Number-based Community Health Service (LKM-NIK) policy supports the principles of New Public Service (NPS) in increasing access to health insurance in Bekasi City has a strong influence in increasing access to health and health services to the community. Second, LKM-NIK provides maximum results in improving health services in Bekasi City by using the concept of integrating health services with democratic values and social justice which refers to the concept of New Public Service (NPS).